Acceptability of clinics for sexually transmitted diseases among users of the "gay scene" in the West Midlands. Issue 4 (August 1997) - Hope, V D; MacArthur, C
Abstract : OBJECTIVES: To examine the acceptability of genitourinary medicine (GUM) clinics (for STDs) to homosexual and bisexual men. DESIGN: A cross sectional survey of men using "gay" venues and groups in the West Midlands region of the UK. Data were collected using an anonymous self-completed questionnaire. RESULTS: 848 completed questionnaires were returned. Two thirds of the respondents reported "safer" sexual behaviour. Those who had ever attended a GUM clinic (55%) differed little in their safer sexual behaviour from those who had never attended. The acceptability of the service was assessed using a range of indicators: the majority of the attendees had told a doctor, nurse or health adviser they have sex with men; and just over half had found all staff to be friendly, helpful or not homophobic. A quarter of attendees found talking about sexual matters difficult; these were less likely to have found the service acceptable. Over half (54%) of the study respondents had not been vaccinated against hepatitis B. Those who had been vaccinated were more likely: to have found the service acceptable; to have found talking about sexual matters easy; and to report safer sexual behaviour. CONCLUSIONS: These findings suggest that many homosexual and bisexual men who may need to use the GUM service have not done so. There is a need to improve the acceptability of the service and to further promote hepatitis B vaccination.